Psychological variables and physical exercise in patients with rheumatoid arthritis - A.B. Dario; W. Külkamp; H.C. Faraco; M.S. Gevaerd; S.C. Domenech (Desafio Singular, 2010)
ABSTRACTThe purpose of this study was to provide a literature review aiming to clarify the most prevalent psychological changes present in individuals suffering from rheumatoid arthritis (RA), the impact of exercise on such changes, and the exercise protocols commonly adopted to improve these individuals' mental health. The few studies available report anxiety disorders and depression as most prevalent and physical exercise as a significant therapeutic strategy for this population. There is some evidence of the beneficial effects of exercise on those psychological variables providing RA patients with more effective treatments.